Pendampingan Pemanfaatan IT Pada Anak Usia Sekolah di Desa Mulyo Sari Kecamatan Tanjung Sari - Karnila, Sri; Oktaviani, Erni; Oktaviani, Asih; Yuni Puspita, Rima (ABDI AKOMMEDIA : JURNAL PENGABDIAN MASYARAKAT, 2024)
This service is carried out for the needs and strategies applied, for school-age children in Mulyo Sari Village, Tanjung Sari District in the utilization of IT (Information Technology) so that they can face the increasingly rapid development of technology. Problems that occur due to a lack of understanding of children in the introduction and use of IT at this time, can hurt children such as decreased motivation to learn, and some are less socialized because they are busy playing gadgets. The benefits of developing technology also have a positive impact, such as being a means and infrastructure for learning in the search for knowledge. To avoid negative consequences, assistance in utilizing technology is excellent. For this reason, it is hoped that the service will assist in utilizing technological developments in school-age children. Pengabdi will share by providing understanding material, and knowledge about the use of IT which is growing rapidly today. This service went well and had a good impact, 10% of the number of school-age children who participated in this service knew and could type using a laptop. Now 95% of school-age children already understand the parts and how to operate a laptop, not only that, but also increased knowledge about healthy IT pattern literacy.